Science Growth and Society: A New Perspective. Report of the Secretary-General's Ad Hoc Group on New Concepts of Science Policy - Organization for Economic Co-operation and Development (Paris, 1971)
This report has bee split in five parts. Part 1: will set out the assumptions made by the Science Policy Group concerning the essential issues surrounding national and international science policy in our time. Part 2: deals with the connections between economic growth, technology, and society. Part 3: attempts to evaluate the achievements, deficiencies, and limitations of science policy in the 1960's. Part 4: suggests a new framework and new approaches to critical issues relating to effective functioning of science policy in the 1970's; and Part 5: presents some recommendations to the Organization for Economic Co-operation and Development (OECD) and its members.
ne 5/03/2018
Loan
Keywords: Science and State